31.4: Invited Paper: Recent Development of Soluble Hole Injection Material for Printed OLED and QLED Display. (4th October 2019) - Monzen, Kazuhiro; Maeda, Daisuke; Higashi, Masayuki; Endo, Toshiyuki
Abstract : We are developing the soluble hole injection materials and the inks, named ELsource ® that can be used as hole injection layer in OLED display. OLED display is one of optical device. Therefore, we developed the hole injection materials with optical properties necessary for that optical devices. We also developed the hole injection material with the deeper ionization potential applicable to QLED display.